Reproducibility of Functional MR Imaging Results Using Two Different MR Systems - Vlieger, Erik-Jan; Lavini, Cristina; Majoie, Charles B.; den Heeten, Gerard J. (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: In the application of functional MR imaging for presurgical planning, high reproducibility is required. We investigated whether the reproducibility of functional MR imaging results in healthy volunteers depended on the MR system used.METHODS: Visual functional MR imaging reproducibility experiments were performed with 12 subjects, by using two comparable 1.5-T MR systems from different manufacturers. Each session consisted of two runs, and each subject underwent three sessions, two on one system and one on the other. Reproducibility measures D (distance in millimeters) and Rsize and Roverlap (ratios) were calculated under three conditions: same session, which compared runs from one session; intersession, which compared runs from different sessions but from the same system; and intermachine, which compared runs from the two different systems. The data were averaged per condition and per system, and were compared.RESULTS: The average same-session values of the reproducibility measures did not differ significantly between the two systems. The average intersession values did not differ significantly as to the volume of activation (Rsize), but did differ significantly as to the location of this volume (D and Roverlap). The average intermachine reproducibility did not differ significantly from the average intersession reproducibility of the MR system with the worst reproducibility.CONCLUSION: The location of activated voxels from visual functional MR imaging experiments varied more between sessions on one MR system than on other MR system. The amount of the activated voxels is independent of the MR system used. We suggest that sites performing functional MR imaging for presurgical planning measure the intersession reproducibility to determine an accurate surgical safety margin.